Trabalho informal : saberes e experiências dos trabalhadores da Associação Matogrossense dos Artesãos - Ramirez, Michele Bruno (2015)
Informal work in “Association Matogrossense of Artisans”, suffers influence of capitalism and specifically the neoliberalism in precarious work. The Macroeconomic reforms and the expansion of neoliberal policies expand privatization, undermine public services and increases unemployment. In this scenario the goal is to reflect on the work as an educational principle and training knowledge, experiments and all that is experienced for artisans ensure the production of their lives. The field research was based on experiences and knowledge workers' “Association Matogrossense of Artisans”, based the historical and dialectical materialism that presuppose from a reality historical and material to achieve our goal. From the research qualitative used the technique of observation systematic, the application of open-ended questionnaire and semi-structured interviews. In this context, the informal work of artisans becomes one of survival alternatives, an option on low wages, exploitation of bosses and resistance, the entrepreneurial spirit within an exclusionary social system. Working in an informal association of artisans is a way of generating income, freedom of choice in production form, however, implies living with discrimination, instability, precariousness of coverage of basic rights. On the offensive of capital with his stance intensification exploitation of the workforce, creation of structural unemployment increasing the reserve army of labor and unemployed, the activity of these informal workers indicates the implementation of a strategy for the production of life material and immaterial of men and women popular sectors while, brings out an existence permeated by the construction of knowledge from experience.